Inflammation and immunity in IPF pathogenesis and treatment. (February 2019) - Heukels, P.; Moor, C.C.; von der Thüsen, J.H.; Wijsenbeek, M.S.; Kool, M.
Abstract: Idiopathic pulmonary fibrosis (IPF) is a progressive, and ultimately fatal, chronic interstitial lung disease characterized by enhanced extracellular matrix deposition. Repetitive alveolar epithelial injury triggers the early development of fibrosis. These injuries, in combination with dysregulated wound repair and fibroblast dysfunction, lead to ongoing tissue remodelling and fibrosis seen in end-stage pulmonary fibrosis. Although the exact etiology in IPF is unknown and probably diverse, all stages of fibrosis are accompanied by innate and adaptive immune responses. The role of inflammation as an important component in IPF etiology is controversial and sometimes seen as an epiphenomenon of fibrosis. This view is partly the result of negative multicenter trials of anti-inflammatory drugs for IPF treatment. However, new insights on the role of macrophages, the loss of T-cell and B-cell tolerance leading auto-immune responses in IPF, and the interaction of immune cells with (myo)fibroblasts have led to a slow change of this opinion. Clearly, more insight is needed to integrate basic immune mechanisms into translational research and finally new IPF therapies. In this concise review, we will focus on the role of our innate and adaptive immune system in the initiation and perpetuation of IPF pathobiology. Next, we will discuss how immune responses are influenced by current anti-fibrotic treatments, such as pirfenidone and nintedanib and end with an overview of recent and upcoming therapeutic trials that target and modulate our immune system in patients with IPF. Highlights: IPF is a progressive fibrosing interstitial lung disease in which innate and adaptive inflammatory processes are activated. This review gives an up-to-date overview of new trials for IPF treatment and their interaction with the immune system.